a)
[tex]1 - \frac{3}{14} = \frac{14}{14} - \frac{3}{14} = \frac{11}{14} [/tex]
[tex]1 - \frac{7}{9} = \frac{9}{9} - \frac{7}{9} = \frac{2}{9} [/tex]
b)
[tex]3 - \frac{1}{4} = 2 \frac{4}{4} - \frac{1}{4} = 2 \frac{3}{4} [/tex]
[tex]5 - \frac{5}{7} = 4 \frac{7}{7} - \frac{5}{7} = 4 \frac{2}{7} [/tex]
c)
[tex]3 \frac{4}{9} - \frac{7}{9} = 2 \frac{13}{9} - \frac{7}{9} = 2 \frac{6}{9} = 2 \frac{2}{3} [/tex]
[tex]2 \frac{7}{12} - 1 \frac{11}{12} = 1 \frac{19}{12} - 1 \frac{11}{12} = \frac{8}{12} = \frac{2}{3} [/tex]